Sleep-Disordered Breathing: A Risk Factor for Adverse Pregnancy Outcomes? - Facco, Francesca L.; Liu, Cici S.; Cabello, Andrea A.; Kick, Ashley; Grobman, William A.; Zee, Phyllis C. (American Journal of Perinatology, 2012)
In nonpregnant populations, sleep-disordered breathing (SDB) has been associated with cardiovascular and metabolic disease. Few studies have examined the relationship between SDB and adverse pregnancy outcomes (APO). The objective of this study was to examine the association between SDB and APO. Women who had a delivery as well as an in-laboratory polysomnogram (PSG) were identified. Demographics, PSG results, and pregnancy outcomes were abstracted from the medical record. Absence of SDB was defined as an apnea hypopnea index (AHI) of <5, mild SDB as an AHI of 5 to 14.9, and moderate to severe SDB as an AHI of ≥15. The primary outcome was a composite measure of APO: pregnancy-related hypertension, gestational diabetes, or preterm birth ≤34 weeks. We identified 143 women who had undergone a PSG and a delivery. Increasing severity of SDB was associated with an increasing risk of the composite APO: AHI <5, 18.1%; AHI 5 to 14.9, 23.5%; AHI ≥15, 38.5% (p = 0.038). Obese women (body mass index ≥30) with moderate to severe SDB had the highest rate of APO, 41.7%. SDB, especially moderate to severe disease, may be associated with APO. However, it is unclear if SDB is a risk factor for APO independent of obesity.
Keywords: sleep disordered breathing; sleep apnea; pregnancy